Konstruksi Sosial Penundaan Tugas Akademik Mahasiswa di Era Digital - Hermansyah Hermansyah; Rasuna Amirudin Dasing; Gazali Husin Rengiwur (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
Digital transformation in higher education has reshaped learning patterns and students’ academic practices, including how they manage and complete academic tasks. On the one hand, digital learning offers flexibility and easy access to learning resources; on the other hand, it has intensified tendencies toward academic task procrastination. This study aims to analyze students’ academic task procrastination as a socially constructed reality within the context of digital learning. The research adopts a qualitative approach with a case study design conducted at IAIN Fattahul Muluk Papua. Data were collected through in-depth interviews with students and lecturers and analyzed using Peter L. Berger and Thomas Luckmann’s social construction theory, encompassing the processes of externalization, objectivation, and internalization. The findings indicate that task procrastination is externalized through flexible learning schedules, digital media distractions, fatigue with instructional methods, and academic pressure. These practices are subsequently objectivated through students’ collective experiences and social relations with lecturers, leading them to be perceived as normative behavior in digital learning. Furthermore, task procrastination is internalized as a habit and an adaptive, taken-for-granted strategy within students’ learning rhythms. This study affirms that academic task procrastination cannot be reduced to an individual problem alone; rather, it emerges from the complex interaction between technological structures, pedagogical practices, and academic social dynamics. The findings are expected to contribute to the development of more reflective and contextual digital learning policies and strategies.